Risk : modelling, assessment & management - Haimes, Yacov Y. (John Wiley & Sons, 2009)
Integrates the art and science of risk analysis.; Clearly shows how to quantify risk and construct probability in conjunction with real-world decision-making problems, including a host of institutional, organizational, political, and cultural considerations.; Presents basic concepts as well as advanced material, avoiding higher mathematics whenever possible.; Incorporates numerous examples and case studies to illustrate the analytical methods under discussion.; An accompanying web site will offer 200 example problems and case studies